The mental health of university students to attitudes toward COVID-19 vaccination - Osama S. Hamdouna; Mohammed R. Al Massri (INSPIRA: Indonesian Journal of Psychological Research, 2022)
The current study aimed to identify the relationship between mental health and the attitudes toward receiving the COVID-19 vaccine. It also aimed to determine the levels of mental health and attitudes towards receiving the COVID-19 vaccine among students of the Faculty of Education at Al-Azhar University, Gaza, Palestine. To achieve the study’s objectives, the researchers used the descriptive approach, and the study sample consisted of 200 students from the Faculty of Education, Al-Azhar University, Gaza, Palestine. The study used the mental health scale, which consists of three dimensions (psychological stress, depression, and anxiety) and attitudes toward receiving the COVID-19 vaccine scale; it consists of three dimensions (cognitive, behavioral, and emotional), and the researchers prepared such scales. Through SPSS, The results showed a positive relationship between mental health and attitudes towards receiving the COVID-19 vaccine among students of the Faculty of Education at Al-Azhar University, and the level of mental health at the total degree was medium. The story of trends towards receiving the COVID-19 vaccine, on the entire degree, was medium. According to the research outcomes, the researchers recommend providing the students with psychological intervention such as counseling and guidance to decrease negative psychological symptoms and upgrade their positive attitude toward the COVID-19 vaccine.